Beyond the Icon, Beyond the Human: An Ecocritical Reading ofFrancis of Assisi across Irish and British Poetry (1960s–2010s) - Rozzoni, Stefano (Jan Kochanowski University Press, 2024)
This paper explores the presence of Francis of Assisi across Irish and British literature from the 1960s to the 2010s, through the study of a poetic trajectory centring on a popular episode in his hagiography known as ‘the preaching to the birds’. Through an ecocritical lens, my analysis investigates how this narrative entails the theme of human–nonhuman relationality revealing the ‘mature environmental aesthetics’ of the poems under examination alongside the rise of ecological discourses in the contexts of their publication. By analysing five poems by different authors–Norman MacCaig, Seamus Heaney, and Michael Longley (1960s), and Paula Meehan and Ann Wroe (1990s–2010s) – this essay gauges how poetic renderings of Francis, beyond mere simplistic assessment of his ‘iconic’ status in contemporary culture, testify to his efficacy, as a poetic subject, to engage with current debates in the environmental humanities. Specifically, I discuss how, in the selected poems, Francis fosters a paradigm shift to still-dominant mental and physical habits that have led to the Anthropocene in conceiving humans and nonhumans beyond anthropocentric, dualistic figurations, while acknowledging forms of ontological and material continuity among them.